One of the good ones - Moulite, Maika; Moulite, Maritza (Inkyard Press, 2021)
Although distraught, Happi is also unsettled by the way people have idealized the memory of her sister who was killed after attending a social justice rally -- why do people have to be perfect in order to be missed? As a way to honor the memory, however, Happi and her other sister Genny go on a roadtrip using the original "Green Book" -- but the trip reveals secrets neither sister knew about the dead Kezi.